2022
DOI: 10.1093/oxfimm/iqac005
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 immunity and vaccine strategies in people with HIV

Abstract: Current SARS-CoV-2 vaccines, based on the ancestral Wuhan strain, were developed rapidly to meet the needs of a devastating global pandemic. People living with HIV (PLWH) have been designated as a priority group for SARS-CoV-2 vaccination in most regions and varying primary courses (2 or 3-dose schedule) and additional boosters are recommended depending on current CD4+ T cell count and/or detectable HIV viraemia. From the current published data, licensed vaccines are safe for PLWH, and stimulate robust respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 193 publications
2
18
0
Order By: Relevance
“…The SARS-CoV-2 associated disease (COVID-19) can be developed in asymptomatic or mild forms, but may also cause severe dysregulation, leading to hospitalization and a poor outcome [ 31 ]. PLWH are a category of individuals whose immune dysfunction places them at risk of developing severe COVID-19 [ 22 ], and they represented a very small portion of the cohorts enrolled for the vaccines’ trials [ 13 ]. There are only a few studies reporting data on the vaccine-induced protection in this population [ 23 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SARS-CoV-2 associated disease (COVID-19) can be developed in asymptomatic or mild forms, but may also cause severe dysregulation, leading to hospitalization and a poor outcome [ 31 ]. PLWH are a category of individuals whose immune dysfunction places them at risk of developing severe COVID-19 [ 22 ], and they represented a very small portion of the cohorts enrolled for the vaccines’ trials [ 13 ]. There are only a few studies reporting data on the vaccine-induced protection in this population [ 23 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data on the COVID-19 vaccine efficacy and immunogenicity remain scarce in PLWH [ 22 ]. It has been shown that a third mRNA vaccine dose strongly boosts the humoral immune response in PLWH at higher levels, compared to the post-second dose, regardless of the CD4+ T cell count [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 We and others have previously shown a failure to mount a robust antibody response following COVID-19 vaccination in advanced HIV infection with low CD4 T cell counts below 200 cells/µl. [8][9][10][11][12] Data on vaccine efficacy and immunogenicity in PLWH remains limited (reviewed in 13 ), and while there are some conflicting results, meta-analyses 14 and recent studies 15 have shown reduced levels of seroconversion and neutralization after a second dose of viral vector vaccine dose in PLWH receiving cART, with lower CD4 T cell count/viraemia and older age resulting in a more impaired response and more rapid breakthrough infection. 16 Assessment of vaccine efficacy has been continually complicated by the ongoing emergence of variants of concern (VOC), with the Alpha, Beta, Delta and Omicron variants being observed to progressively evade antibodies 17,18 raised against the original Wuhan-Hu-1 strain in most vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests additional doses/targeted vaccines could be merited, especially given 28% of SARS-CoV-2 naïve PLWH failed to neutralize Omicron after the third vaccine dose. Previous studies among similar cohorts of PLWH with undetectable HIV viral loads have produced mixed results, as previously reviewed (Mullender et al, 2022). SARS-CoV-2 viral vector vaccines have shown similar magnitude and durability of antibody responses to HIV-negative controls (Frater et al, 2021; Ogbe et al, 2022b) but reduced levels of seroconversion and neutralization have been reported after two doses in PLWH in a more recent study (Woldemeskel et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…Data on vaccine efficacy and immunogenicity in PLWH remains limited (reviewed in (Mullender et al, 2022)), and while there are some conflicting results, meta-analyses (Tamuzi et al, 2022) and recent studies (Woldemeskel et al, 2022) have shown reduced levels of seroconversion and neutralization after a second dose of viral vector vaccine dose in PLWH, with lower CD4 T cell count/viraemia and older age resulting in a more impaired response and more rapid breakthrough infection (Sun et al, 2022). Data after three vaccine doses are scarce, especially of evaluating efficacy against Omicron.…”
Section: Introductionmentioning
confidence: 99%